I AS THE OTHER, THE OTHER AS I - Tonyan, Marika (Armenian Folia Anglistika, 2025)
Whatever new approaches to self-identity may appear in scholarly research, the linguistic aspect of the problem remains vitally important. The question of the speaker’s identity (especially in connection with the other), defined and manifested linguistically, relates to the notion of selfhood, which is central for the modern studies of the individual’s place within society. In the canonical situation of speech everything a person says relates to him as to the centre of the communication act, and the temporal-spatial-personal-social coordinates are set by the implicit existence of the speaker. There are cases, however, when this canonical situation is modified, and two of such modifications are in the focus of the paper. In the first case the speaker identifies himself with another person, and as a result the latter is endowed with subjectivity and individualization. The second is reference to oneself in the third person, the so-called illeism, which objectifies one’s selfhood and leads to self-distancing. The two processes result in intricate dynamics of relations that the speaker constructs with oneself and the other, as well as in psychological connotations of these interrelations. The aim of the present research is to examine the semantic and pragmatic issues within these modifications.
Keywords: egocentrism; illeism; self-reference; individualization; identity; social self